Penerapan Metode Waterfall Dalam Perancangan Aplikasi Kasir Berbasis Desktop PT. Lafiye Mode Indonesia - Fairuz Dzulfiqar, Muhammad; Absar Abdallah, Zidan; Reza Pahlevi, Zulfikar; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
As time progresses, technology continues to develop, following the increasing human needs for technology. The demand for computers and application programs has been steadily rising and evolving. In contemporary life, nearly every aspect requires technological assistance, including the aspect of conducting transactions. One of the most frequently used technologies in transactions with clients is the cashier application. Desktop-based cashier applications offer numerous advantages, such as easier accessibility from anywhere and time-saving data processing during sales transactions. PT. Lafiye Mode Indonesia has been conducting its sales transactions using Microsoft Excel, but due to the large volume of data processed, which often amounts to hundreds of entries, errors frequently occur, leading to unrecorded transaction data. Therefore, a cashier application is essential for any business field. This paper presents the design and development of a desktop-based cashier application aimed at recording every sold item and incoming funds more accurately in a database. The desktop-based cashier application will assist PT. Lafiye Mode Indonesia in facilitating transactions with clients and ensuring better-organized data recording, thereby making the administrative system more transparent in all aspects.